The chills as a psychological construct content universe, factor structure, affective composition, elicitors, trait antecedents, and consequences. [article]. - Maruskin, Laura A.
We examined the content universe, factor structure, affective composition, elicitors, trait antecedents, and consequences of "the chills." In study 1, participants described what it means to get chills. A second sample sorted all references to physical sensations based on similarity. Cluster analysis identified 4 lower order clusters (goosebumps, tingling, coldness, shivers) and 2 higher order clusters ("goose tingles," "cold shivers"). In study 2, factor analysis of questionnaire data supported a model with lower and higher order factors that corresponded to the study 1 clusters. Goose tingles and coldshivers were predicted by approach-related traits (e.g., extraversion) and avoidance-related traits (e.g. neuroticism), respectively. In Study 3, analysis of narrative data replicated the goose tingles-coldshivers structure. Relative to cold shivers, goose tingles involved greater awe, surprise, and enjoyment and less disgust, fear, and sadness. In Study 4, analysis of diary data extended the goose tingles-coldshivers structure between- and within-person levels of analysis. Goosetingles involves positive affects and was elicited by avoidance-related stimuli, whereas coldshivers involved negative affects and was elicited by avoidance-related stimuli. In Study 5, manipulation of exposure to self-actualization and self-annihilation elicited goose tingles and cold shivers, respectively. Goosetingles and cold shivers had positive and negative affects, respectively, on interpersonal closeness. In sum, diverse forms of evidence converge to indicate that the chills encompasses distinct approach- and avoidance-related constructs. Failure to distinguish these constructs explains null and inconsistent findings in the nascent literature. Goosetingles and cold shivers are posited to serve the function of signaling that an event in the environment is pertinent to one's most deep-seated hopes or fears.. - (from the authors)
Keywords: THRASH, todd M; Chills; Piloerection; Emotion; Affect; Approach-avoidance motivation